2014
DOI: 10.1002/pbc.24949
|View full text |Cite
|
Sign up to set email alerts
|

Impact of decreased heparin dose for flush‐lock of implanted venous access ports in pediatric oncology patients

Abstract: Children with implanted ports had similar complication rates and care safety measures whether their ports were flushed with 10 units/ml of heparin or 100 units/ml. Standardizing flush-locks to lower doses of heparin may be a promising approach to maintaining port patency without compromising patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The letter by Lee et al provides an interesting anecdote which may support our findings . However, our results and this case would require more robust study designs to provide evidence to support wider adoption of less frequent flush‐locking or the use of normal saline instead of heparin for flush‐lock.…”
supporting
confidence: 74%
“…The letter by Lee et al provides an interesting anecdote which may support our findings . However, our results and this case would require more robust study designs to provide evidence to support wider adoption of less frequent flush‐locking or the use of normal saline instead of heparin for flush‐lock.…”
supporting
confidence: 74%
“…A Cochrane review in adult patients comparing heparin with normal saline flushes found no convincing difference in maintaining CVC patency [146]. After a change in practice, Rosenbluth et al [147] explored the effect of using 100 U/mL v 10 U/mL heparin solution for flushing implantable vascular ports in pediatric oncology patients, and found no difference in complication rates.…”
Section: Interventions To Decrease Thrombotic Complications and Cvc Omentioning
confidence: 99%
“…To the Editor: We read with interest the paper by Rosenbluth et al on the use of heparin saline for the flush‐lock of implanted venous access ports in order to maintenance catheter patency. With the successful use of a reduced concentration of heparin (10 units/ml versus 100 units/ml) for the monthly flush‐lock, a new policy has been implemented that helps to reduce patients' exposure to heparin and thus its potential health hazards.…”
mentioning
confidence: 99%